2009
DOI: 10.1542/peds.2008-2771
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Exposure and Lymphocyte mtDNA Content Among Uninfected Infants of HIV-1-Infected Women

Abstract: OBJECTIVE Concern for potential adverse effects of antiretroviral (ARV) chemotherapy used to prevent mother-to-child HIV transmission has led the US Public Health Service to recommend long-term follow-up of ARV-exposed children. Nucleoside reverse transcriptase inhibitor ARV agents can inhibit DNA polymerase γ, impairing mitochondrial DNA (mtDNA) synthesis and resulting in depletion or dysfunction. METHODS We measured the mtDNA content of stored peripheral blood mononuclear cells (PBMCs) of 411 healthy child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 46 publications
6
48
1
Order By: Relevance
“…The authors found that PBL mtDNA was decreased in HIV-exposed neonates compared to controls, but was higher in ART/ HIV-exposed neonates than HIV-exposed neonates who were not exposed to ART. 71 These data support the notion that HIV itself, and not NRTIs, is the major contributor towards PBL mtDNA depletion. Regarding ART-exposed patients in larger studies, Chiappini et al, 65 Coté et al 68 and De Mendoza et al 66 all found lower levels of PBL mtDNA associated with d4T, DDI and particularly d4T/DDI combination regimens.…”
Section: Research History Of Nucleoside Reverse Transcriptase Inhibitsupporting
confidence: 64%
“…The authors found that PBL mtDNA was decreased in HIV-exposed neonates compared to controls, but was higher in ART/ HIV-exposed neonates than HIV-exposed neonates who were not exposed to ART. 71 These data support the notion that HIV itself, and not NRTIs, is the major contributor towards PBL mtDNA depletion. Regarding ART-exposed patients in larger studies, Chiappini et al, 65 Coté et al 68 and De Mendoza et al 66 all found lower levels of PBL mtDNA associated with d4T, DDI and particularly d4T/DDI combination regimens.…”
Section: Research History Of Nucleoside Reverse Transcriptase Inhibitsupporting
confidence: 64%
“…Several studies showed a depressed hematopoiesis in HEU children, including a decrease in platelets, neutrophils, total lymphocytes, CD4 and CD8 ϩ cell count, 21,22,24,51,52 that might be attributable to mitochondrial dysfunction associated with exposure to nucleoside reverse transcriptase inhibitors (NRTIs). Indeed, NRTIs cross the placenta 53,54 and have an affinity for the mitochondrial ␥ polymerase. It has been shown that mitochondrial DNA of cord blood mononuclear cells is significantly reduced in HEU infants compared with infants who are born to HIVuninfected mothers, 53 and the majority of infants who are exposed to NRTI present transient and asymptomatic hyperlactatemia 55,56 ; however, persistent mitochondrial dysfunction that leads to severe neurologic impairment has been reported in a limited number of HEU infants.…”
Section: Discussionmentioning
confidence: 99%
“…The few studies on long‐term HAART exposure have focused on foetal and perinatal ARV effects 32, 33, 34, 35, 36, 37, but rarely on maternal‐related problems which may, in turn, affect children.…”
Section: Introductionmentioning
confidence: 99%